DIGITAL ECONOMIC TRANSFORMATION IN SOUTHEAST SULAWESI PROVINCE - Puspa Dewangga; Zainuddin Saenong (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the development of the digital economy in Southeast Sulawesi Province. The research uses a qualitative descriptive approach with secondary data obtained from the Central Statistics Agency, Bank Indonesia, scientific journals, and related publications. The study focuses on non-cash payment systems, QRIS usage, e-commerce businesses, and digital infrastructure. The results show that the digital economy has experienced positive growth, indicated by increasing non-cash transaction values, growth in QRIS merchants and users, and a rising number of e-commerce businesses. However, challenges remain, including internet access disparities, limited digital infrastructure, and low digital literacy in some areas. Collaboration among the government, private sector, and society is essential to support inclusive and sustainable digital economy development in Southeast Sulawesi Province